Kecurangan Akademik Dalam Perspektif Teori Fraud Diamond - Devi Maya Sofa; Endah Susilowati (RELASI : JURNAL EKONOMI, 2021)
Academic fraud can occur in university because it is influenced by various underlying factors, both internally and externally. The purpose of holding this study was to determine whether the pressure, opportunity, rationalization, and abilities possessed by students significantly influence the occurrence of academic fraud in university. This research was conducted on 92 students of the Accounting Major in East Java "Veteran" National Development University by filling out a questionnaire via Google Form. The results of data collection were processed statistically using SmartPLS. The results of data analysis show that pressure, rationalization, and ability have a significant effect on academic fraud, while opportunities do not significantly influence students because lecturers always provide objective assessments to students, thereby reducing the chance of academic fraud. Keywords: Diamond Fraud Theory, Academic Fraud